Yolk-shell structured CuSi2P3@Graphene nanocomposite anode for long-life and high-rate lithium-ion batteries. (February 2021) - Li, Wenwu; Ma, Qibin; Shen, Pengfei; Zhou, Yucun; Soule, Luke; Li, Yunyong; Wu, Yanxue; Zhang, Haiyan; Liu, Meilin
Abstract: Silicon-based anode materials enable the development of commercial lithium-ion batteries (LIBs) with higher gravimetric energy densities than are currently available. However, the inherently low electronic and ionic conductivity as well as large volume expansion upon lithiation of Si hinder their use in practical applications. Here we report a cation-disordered CuSi2 P3 material, synthesized using high-energy ball milling, that shows improved stability, larger capacity, and higher ionic and electronic conductivity than pure Si. When used as an anode for LIBs, CuSi2 P3 demonstrates a high reversible capacity of 2069 mA h g −1 with an initial Coulombic efficiency of 91% and a suitable working potential of 0.5 V (vs. Li + /Li). Further, after a two-step ball milling of CuSi2 P3 with graphite, a yolk-shell structured carbon-coated CuSi2 P3 @graphene nanocomposite is formed that shows enhanced long-term cycling stability (1394 mA h g −1 after 1500 cycles at 2 A g −1 ; 1804 mA h g −1 after 500 cycles at 200 mA g −1 ) and rate capability (530 mA h g −1 at 50 A g −1 ), surpassing those for other Cu-Si, Cu-P, and Si-P compounds or single-component Si- and P-based composites. When coupled with a LiNi0.5 Co0.2 Mn0.3 O2 (NCM) cathode in a full cell, the NCM//CuSi2 P3 @graphene battery exhibits a high capacity of 140 mA h g −1 after 200 cycles, demonstrating the potential of CuSi2 P3 anodes for the next-generation high-performance LIBs. Graphical Abstract: Ternary CuSi2 P3 has high electronic conductivity and low Li-ion diffusion energy barrier, thus delivering better Li-storage properties than related binary and single-component electrodes. ga1 Highlights: Ternary CuSi2 P3 has high electronic conductivity. CuSi2 P3 has a low Li-ion diffusion energy barrier. CuSi2 P3 shows better Li-storage properties than related binary and single-component electrodes studied. A dual-carbon protection architecture is created by a two-step ball milling process. A full battery based on CuSi2 P3 /C anode also shows long-term cycling stability.